Dimensions of physical punishment and their associations with children's cognitive performance and school adjustment. (January 2018) - Font, Sarah A.; Cage, Jamie
Abstract: This study examined how a range of physical punishment measures, ranging from mild corporal punishment to physical abuse, are associated with cognitive performance, school engagement, and peer isolation over a 3- year span among 658 children initially observed between the ages of 8 and 14. Physical punishment was captured in three groups: mild corporal punishment, harsh corporal punishment, and physical abuse, and both caregiver- and child-reported punishment measures were considered. After accounting for socioeconomic and demographic characteristics, only Ninitial exposure to physical abuse was significantly associated with declines in cognitive performance. However, all forms of physical punishment were associated with declines in school engagement, and harsh corporal punishment was associated with increased peer isolation. Our findings were relatively consistent regardless of whether physical punishment was reported by the child or caregiver. Overall, our findings suggest that the prevention of physical abuse may enhance children's cognitive performance, but that alone may not be sufficient to ensure children are engaged and well-adjusted in school.